G22 Duodenal stricture as a rare, possible complication of eosinophilic gastrointestinal disease (EGID). (12th September 2022) - Mardare, Roxana; Kadir, Ahmed; Naik, Sandhia; Jellis, Laura; Deb, Protima; Gasparetto, Marco
Abstract : EGID is a recently described condition with an unknown etiology and pathogenesis. There are three case reports of duodenal stricture associated with EGID: one in an adult requiring pancreaticoduodenectomy due to the suspicion of malignancy and 2 cases in a child and a young adult, who responded to oral steroids. We report the case of a 10-year-old who presented to A&E with a 9-month history of epigastric abdominal pain and 1 episode of haematemesis, on a background of asthma. He was treated for Helicobacter pylori, based on a positive stool antigen. Abdominal pain and vomiting persisted, therefore an oesophago-gastro-duodenoscopy (OGD) was performed. This identified widespread white plaques throughout the oesophagus, erythema and nodularity of the gastric antrum and white nodules in the first part of the duodenum. Histology revealed changes of EGID and eosinophilic oesophagitis (EOE) and patient was commenced on Montelukast, oral viscous Budesonide (OVB), Cetirizine and continued proton pump inhibitor (PPI). After the allergy workup identified house dust mites, cat sensitisation and fish allergy, a 6-food elimination diet was initiated. During the next 2 years, symptoms subsided, and endoscopy changes improved, with only mild signs of active EOE while on OVB, PPI and diary/egg/fish free diet. However, the patient relapsed due to poor compliance to treatment. He became more unwell during the Covid pandemic with recurrent vomiting and static weight. A trial of dupilumab was considered, however his reassessment OGD had to be delayed due to restricted access to theatre. He was treated empirically with a reducing course of oral prednisolone, with temporary response. The endoscopic assessment performed subsequently showed erythema, erosions and white plaques in the distal oesophagus and gastric antrum with narrowing between the first and the second part of the duodenum (D2), that could not be entered. Histology identified mild upper oesophagitis (4 eosinophils(eos)/HPF), active middle and lower oesophagitis (20 eos/HPF and 12 eos/HPF, respectively), chronic gastritis (80 eos/HPF) and nonspecific reactive changes of the proximal duodenum. A barium meal confirmed a duodenal stricture. At this stage, we recommended a sloppy diet and a second weaning course of oral prednisolone, along with Montelukast. He was subsequently commenced on azathioprine for maintenance of remission. A repeat barium study and small bowel MRI performed post course of steroids and on azathioprine revealed stable appearances of the proximal duodenal stricture, excluding the presence of further strictures. While the patient has responded to the course of oral steroids and azathioprine, a repeat upper GI endoscopy is currently planned to dilate the duodenal stricture. The challenges posed by this case were the rarity of the condition, limited treatment options and access to endoscopy during the Covid pandemic and the fact that unlike previous case reports a sustained remission could not be obtained on steroids, and a maintenance immunosuppressive medication was required. We can conclude that this subgroup of patients should be monitored closely for signs of bowel obstruction and will require more intense treatment, including immunomodulators, endoscopic dilatation and or surgery. References: Kinoshita Y, Oouchi S, Fujisawa T. Eosinophilic gastrointestinal diseases - Pathogenesis, diagnosis, and treatment. Allergol Int 2019 Oct;68 (4):420–429. doi: 10.1016/j.alit.2019.03.003. Epub 2019 Apr 16. PMID: 31000445. Jin H, Slater K. Pancreaticoduodenectomy for stricturing primary eosinophilic duodenitis. BMJ Case Rep 2021 May 10;14 (5):e240101. doi: 10.1136/bcr-2020-240101. PMID: 33972297; PMCID: PMC8112431. Somani P, Sharma M, Shastri C, Patil A, Al Khatry M. Multiple duodenal strictures due to eosinophilic duodenitis. Am J Gastroenterol 2017 Mar;112 (3):412. doi: 10.1038/ajg.2016.467. PMID: 28270676. Tan HL, Sithasanan N, Foley P, Davidson GP. The successful medical management of severe duodenal strictures secondary to eosinophilic gastroenteritis in an infant. Pediatr Surg Int 2003 Sep;19 (7):562–3. doi: 10.1007/s00383-003-0995-4. Epub 2003 Aug 2. PMID: 12905002.